Answer: 2
Step-by-step explanation:
Answer:
x = a²
Step-by-step explanation:
To undo the square root, you have to square both sides of the equation so it becomes...
(√x )² = a²
That undoes the square soot so it is
x = a²
Simplify this expression. (2/x-y) + (3/x+y) - (5/y+x) - (7x-9y/y^2-x^2) = ___________/ y^2 - x^2
Answer:
(5y-17x)/ (y^2-x^2)
Step-by-step explanation:
(2/x-y) + (3/x+y) - (5/y-x) - (7x-9y/y^2-x^2) =
Get a common denominator of y^2 - x^2
2/ (x-y) = -2 /( y-x) * (y+x)/(y+x) = (-2y -2x) / (y^2 -x^2)
(3/x+y) = 3/ (x+y) * (y-x)/(y-x) = (3y-3x) / (y^2 -x^2)
-5/(y-x) = -5/(y-x) *(y+x)/(y+x) = -5y-5x / (y^2 -x^2)
- (7x-9y/(y^2-x^2) = -7x +9y/ (y^2-x^2)
Combine the numerators since the denominators are equal
-2y -2x +3y-3x-5y-5x-7x+9y
5y-17x
Put this over the denominator
(5y-17x)/ (y^2-x^2)
Answer:
[tex] \frac{ - 17x + 5y}{ {y}^{2} - {x}^{2} } [/tex]
Solution,
[tex] \frac{2}{x - y} + \frac{3}{x + y} - \frac{5}{y - x} - \frac{7x - 9y}{ {y}^{2} - {x}^{2} } \\ = \frac{2}{x - y} + \frac{3}{x + y} - \frac{5}{ - (x - y)} - \frac{7x - 9y}{ {y}^{2} - {x}^{2} } \\ = \frac{2}{x - y} + \frac{3}{x + y} + \frac{5}{x - y} - \frac{7x - 9y}{ {y}^{2} - {x}^{2} } \\ = \frac{2}{x - y} + \frac{5}{x - y} + \frac{3}{x + y} - \frac{7x - 9y}{ {y}^{2} - {x}^{2} } \\ = \frac{2 + 5}{x - y} + \frac{3}{x + y} - \frac{7x - 9y}{ {y}^{2} - {x}^{2} } \\ = \frac{7}{x - y} + \frac{3}{x + y} - \frac{7x - 9y}{ {y}^{2} - {x}^{2} } \\ = \frac{7(x + y) + 3(x - y)}{(x - y)(x + y)} - \frac{7x - 9y}{ {y}^{2} - {x}^{2} } \\ = \frac{7x + 7y + 3x - 3y}{ {x}^{2} - {y}^{2} } - \frac{7x - 9y}{ {y}^{2} - {x}^{2} } \\ = \frac{10x + 4y}{ {x}^{2} - {y}^{2} } - \frac{7x - 9y}{ {y}^{2} - {x}^{2} } \\ = \frac{10x + 4y}{ - ( {y}^{2} - {x)}^{2} } - \frac{7x - 9y}{ {y}^{2} - {x}^{2} } \\ = \frac{ - 10x - 4y - 7x + 9y}{ {y}^{2} - {x}^{2} } \\ = \frac{ - 10x - 7x - 4y + 9y}{ {y}^{2} - {x}^{2} } \\ = \frac{ - 17x + 5y}{ {y}^{2} - {x}^{2} } [/tex]
hope this helps...
Good luck on your assignment...
A 26-foot ladder is placed against a house and reaches the 24-foot roof. What is the distance between the base of the ladder and the base of the house if the ground meets the house at a right angle?
Answer:
The distance from the base of the ladder to the base of the house is 10ft
Step-by-step explanation:
From the question, we can gather that the ladder makes a right angle shape with the wall of the house.
The length of this ladder which represents the hypotenuse of the right angled triangle is 26ft while the height of the house to the roof is 24ft
To calculate the distance between the base of the ladder and the base of the house, we shall be employing the use of Pythagoras’ theorem which states that the square of the hypotenuse equals the sum of the square of the 2 other sides
We have established that the hypotenuse is the length of the ladder which is 26ft
Let the distance we want to calculate be d
26^2 = 24^2 + d^2
d^2 = 26^2 -24^2
d^2 = 676 - 576
d^2 = 100
d = square root of 100
d = 10ft
Answer:
10
Step-by-step explanation:
24^2 = 576
26^2 = 676
676 - 576 = 100
the square root of 100 is 10 so the answer is 10
What is 200+20000000
Answer:20000200
Step-by-step explanation:
Answer: 20000200
You just add 200 to the larger number.
PLZ HELP I'VE BEEN STUCK FOR A LONG TIME PLZ HELP
(c-d)/5 - 2 = 0
c-6d=0
Given the equations, what is the value of c/d?
PLZ HELP WILL MARK BRAINLIEST
Answer:
c/d = 6
Step-by-step explanation:
Use the second equation.
c - 6d = 0
Add 6d to both sides.
c = 6d
Divide both sides by d.
c/d = 6
help me hahahahahahhahahahaha
which counterexample shows that the conjecture "all mammals live on land" is false?
Answer:
B. A whale is a mammal that does not live on land.
Step-by-step explanation:
Self explanitory
what are three algebra equations whose solution is x=3 ??
Answer:
2x=6
2x+1=7
2x-1=5
Answer:
7-x=4 Solve for x
6/x=2 Solve for x
8x=24 Solve for x
Step-by-step explanation:
LAST TRY!!!! I HAVE THIS LAST QUESTION AND 4 MIMNTES LEFT!!!!!! PLS HELP OUT!!! WILL GIVE BRANLIEST!!! AT LEAST TAKE A LOOK!!! SHARE YO SMARTNESS! ONLY IF YOUR 100% SURE!
Which angles would apply to the consecutive exterior angles theorem?
A) 1 and 7; 2 and 8
B) 1 and 8; 2 and 7
C) 1 and 5; 3 and 7
D) 2 and 6, 4 and 8
Answer:
Step-by-step explanation:
Consecutive exterior angles lie outside on the same side of a transversal.
So it should be 3,45 and 6
Please help me!!!!!!
Answer:
16.7 cm
Step-by-step explanation:
So B = 180 -A-C=180-58-75=47degree
sinB/AC = sinC/AB
sin47/AC=sin75/22
AC=16.65cm
lainey bought a set of 15 makers for $6 what is the cost of 1 marker
Answer:
Each marker costs $.40 or 40 cents
Step-by-step explanation:
Take the total cost and divide by the number of markers
$6.00 /15
.40
Each marker costs $.40 or 40 cents
What is 9/2 in a percentage
Answer:
450%
Step-by-step explanation:
Answer:
450%
Step-by-step explanation:
5 (2 x +1)-2=6x+5
Can someone help solve this
Olga flips 2 fair coins. What is the probability of obtaining a different result on each coin?
Answer:
2/4
Step-by-step explanation:
Probability of obtaining a different result on each coin is [tex]\frac{1}{2}[/tex].
What is probability?Probability means possibility. It is a branch of mathematics that deals with the occurrence of a random event. The value is expressed from zero to one.
Given
Olga flips 2 fair coins.
Probability of obtaining a different result on each coin
Total Number of favorable outcomes = {HH,TT,TH,HT} = 4
Number of favorable outcomes = {HT,TH} = 2
P(E) = [tex]\frac{Total Number of favorable outcomes }{Number of favorable outcomes}[/tex]
P(E) = [tex]\frac{2}{4}[/tex]
P(E) = [tex]\frac{1}{2}[/tex]
Thus, Probability of obtaining a different result on each coin is [tex]\frac{1}{2}[/tex].
Find out more information about Probability here
https://brainly.com/question/11234923
#SPJ3
Express 250 ml as a percentage of 2 litres.
f(x)=4x+1 and g(x)=x^2-5find(f-g)(x)
Answer:
-x²+4x +6Step-by-step explanation:
Given f(x)=4x+1 and g(x)=x²-5
(f-g)(x) is derived by taking the difference of both functions
(f-g)(x) = f(x)-g(x)
(f-g)(x) = 4x+1 - (x²-5)
(f-g)(x) = 4x+1-x²+5
(f-g)(x) = -x²+4x +6
This gives the requires expression
Write each ratio or rate as a fraction in simplest terms. 2) 51 minutes to 21 minutes
Answer:
[tex]\frac{17}{7}[/tex]
5/4 x (54/48 + 105/75)
Answer:
5/4 x (54/48 + 105/75)
= 5/4 x (9/8 + 7/5)
= 5/4 x (45/40 + 56/40)
= 5/4 x 101/40
= 1/4 x 101/8
= 101/32
Hope this helps!
:)
Answer: 3/5/32
Step-by-step explanation:
5/4 x(54/48 + 105/75)
5/4 x (1/1/8 + 1/2/5)
5/4 x 2/21/40
1/1/4 x 2/21/40
3/5/32 ( 3 whole and 5 over 32)
HOPE THIS HELPS
Mark me as the brainiest answer
A group of 6 friends of varying ages meets at a coffee shop and sits in a circle. What is the probability that the
youngest member of the group sits in the seat closest to the door?
Answer:
[tex]100.00 \div 6 [/tex]
The probability that the youngest member of the group sits in the seat closest to the door 1 / 6
Given that, a group of 6 friends of varying ages meets at a coffee shop and sits in a circle, we need to find the probability that the youngest member of the group sits in the seat closest to the door,
So, the probability = favorable outcomes / total outcomes
Here, the favorable outcome = 1
The total outcomes = 1, 2, 3, 4, 5, 6 = 6
So, the probability = 1/6 = 1/2
Hence, the probability that the youngest member of the group sits in the seat closest to the door 1 / 6
Learn more about probability click;
https://brainly.com/question/30034780
#SPJ2
PLEASE ANSWER---
Sandra rolls 2 fair dice.
What is the probability of both dice showing an even number?
Answer:
50 Persent
Step-by-step explanation:
Each one has 3 even and 3 odd numbers.
For the first one to be even there is a 3/6 probability, which reduces to 1/2.
The probability of the second one being even is also 1/2.
The probability of both being even would be 1/2 x 1/2 = 1/4 probability
A cell phone plan costs $200 to start. Then there is a $50 charge each month.Is there a proportional relationship between time and the cost of the cell phone plan? Explain your answer.
Answer:
No because there is a initial cost of $200.
Answer:
see below
Step-by-step explanation:
The equation is
y = 200+50x
This is not a proportional relationship because it does not go through the origin
If x=0, y does not equal 0
Which point lies on the circle represented by the equation (x − 3)2 + (y + 4)2 = 62? A. (9,-2) B. (0,11) C. (3,10) D. (-9,4) E. (-3,-4)
The Answer Is: E: -3,-4
A circle can be characterized by its center's location and its radius's length. The point that lies on the circle is represented by the equation (x−3)² + (y+4)² = 6² is (-3,-4).
What is an equation of a circle?A circle can be characterized by its center's location and its radius's length.
Let the center of the considered circle be at (h,k) coordinate.
Let the radius of the circle be 'r' units.
Then, the equation of that circle would be:
(x-h)² + (y-k)² = r²
If a circle is graphed with the equation on the graph, also, all the points given are graphed, then it can be observed that the only point that lies on the circle is (-3,-4).
Hence, the point that lies on the circle is represented by the equation (x−3)² + (y+4)² = 6² is (-3,-4).
Learn more about the equation of a circle here:
https://brainly.com/question/10165274
#SPJ2
PLEASE HELP I HAVE TO GET THIS DONE IN 10 MINUTES
(07.04A)
Morgan and Leigh spend a certain amount of money from their money box each month to buy plants.
The table shows the relationship between the amount of money (y) remaining in Morgan's money box and the number of months (x):
Function 1
Number of Months
(x) Amount Remaining (in $)
(y)
1 50
2 40
3 30
4 20
The equation shows the relationship between the amount of money (y) remaining in Leigh’s money box and the number of months (x):
Function 2:
y = −9x + 60
Which statement explains which function shows a greater rate of change?
Choices:
Function 1 shows a greater rate of change, because Morgan spends $10 each month and Leigh spends $9 each month.
Function 1 shows a greater rate of change, because Morgan spends $10 each month and Leigh spends $60 each month.
Function 2 shows a greater rate of change, because Morgan spends $10 each month and Leigh spends $60 each month.
Function 2 shows a greater rate of change, because Morgan spends $50 each month and Leigh spends −$9 each month.
Answer:
Function 1 shows a greater rate of change, because Morgan spends $10 each month and Leigh spends $9 each month.
Step-by-step explanation:
The blue points are function one, the black line is function 2.
Find the product of 3/8 and reciprocal of - 5/11
[tex]reciprocal \: of \: \frac{ - 5}{11} \: is \frac{ - 11}{5} \\ product \: of \: \frac{ - 11}{5} \times \frac{3}{8} = \frac{ - 33}{40} \\ hope \: it \: helped \: [/tex]
hope it helps you if it does please mark me as brainliest :-)The height of a trapezoid is 4 in. And its area is 48 in 2. One base of the trapezoid is 6 inches longer than the other base. What are the length of the bases? Complete the explanation on how you found your answer
Answer:
9 inches and 15 inches
Step-by-step explanation:
The height of a trapezoid is 4 in.
Its area is 48 in^2.
Let a be one base and b be the second base.
One base is 6 inches longer than the other. This implies that:
a = 6 + b _________ (1)
The formula for the area of a trapezoid is given as:
[tex]A = \frac{1}{2}(a + b)h[/tex]
where h = height
From (1), we have that:
[tex]A = \frac{1}{2}(6 + b + b )h\\ \\A = \frac{1}{2}(6 + 2b )h[/tex]
We have that h = 4 and A = 48 in^2, therefore:
[tex]48 = \frac {1}{2}(6 + 2b) * 4\\ \\96 = 24 + 8b\\\\8b = 96 - 24 = 72\\\\b = 72 / 8 = 9 in[/tex]
=> a = 6 + 9 = 15 in
The bases are 9 inches and 15 inches long.
Mr. Carson traveled from his house in Pennsylvania to a ski resort in upstate New York. He drove 4.25 hours at a rate of 54.6 miles per hours. When a friend asked how far he traveled to get to the resort, Mr. Carson said “about 2,320 miles.” Mr. Carson actually traveled a distance of . Was Mr. Carson’s estimate reasonable?
Answer:
232.05 miles, no Mr. Carson’s did not estimate reasonable
Step-by-step explanation:
Please answer correctly !!!!!!!!!!!! Will mark brainliest !!!!!!!!!!!!!
Answer:
x = -3/2 x =0
Step-by-step explanation:
(2x+3) ^2 - 6x-9 = 0
Factor out -3 from the last 2 terms
(2x+3) ^2 - 3( 2x+3) = 0
Let m = 2x+3
m^2 - 3m = 0
Factor out m
m(m-3) =0
Using the zero product property
m=0 m-3 =0
m=0 m=3
Substitute 2x+3 back in for m since we are looking for the value of x
2x+3 =0 2x+3 =3
2x +3-3=0-3 2x+3-3=3-3
2x = -3 2x=0
x = -3/2 x =0
PLEASE HELP!
-
FILL IN THE BLANK TO THE RIGHT TO CREATE THE RADICAL THAT WOULD SIMPLIFY TO THE RADICAL INDICATED.
Answer:
180
Step-by-step explanation:
The square root of the number 180 would render the simplified radical expression: [tex]6\,\sqrt{5}[/tex]
We start by factoring completely the number 180:
[tex]180=2^2\,\,3^2\,\,5\\then:\\\sqrt{180} =\sqrt{2^2\,\,3^2\,\,5} \\\sqrt{180} =\sqrt{2^2}\,\,\sqrt{3^2}\,\,\sqrt{5}\\\sqrt{180} =2\,*\,3\,\sqrt{5}\\\\sqrt{180}=6\,\sqrt{5}[/tex]
PLEASE HELP! WILL MARK BRAINLIST!!!
Find the volume of the sphere. Either enter an exact answer in terms of π or use 22/7 for pi. (radius is 1/2)
Answer:
1/6π units³ or 11/21 units³
Step-by-step explanation:
V = 4/3 πr³
r= 1/2
V= 4/3π* (1/2)³= 1/6πor
V= 1/6 *22/7= 11/21Answer:
1/6
Step-by-step explanation:
St
Problems
1 1.3 - (-2.5)
يا
إجابة:
3.8
شرح خطوة بخطوة:
[tex]1.3 - (-2.5)[/tex]
[tex]=1.3+2.5[/tex]
[tex]=3.8[/tex]
Answer:
3.8
Step-by-step explanation:
negative by negative = positive.
1.3 + 2.5 = 3.8
What is the area of this shape
Answer:
179 + 49+ 139 = 367
Step-by-step explanation: